Successful treatment of acute circulatory failure of unknown cause using critical ultrasound-guided reverse fluid resuscitation: A case report. Issue 51 (18th December 2020) - Zhao, Haotian; Long, Ling; Wang, Zekai; Yan, Yaru; Zhao, Heling
Abstract: Rationale: Fluid resuscitation manages shock effectively. However, shock is not always caused by hypovolemia; various types of shock have variable volumetric reactivity. Combined echocardiography and lung ultrasound (LUS) is a new technique for assessing volume status and pulmonary edema in these patients. We report a case of unexplained acute circulatory failure and acute kidney injury (AKI) aggravated by active fluid resuscitation. We used the critical consultation ultrasonic examination (CCUE) protocol for evaluation, and successfully revived the patient with reverse fluid resuscitation. Patient concerns: An 82-year-old man with hypertension, atrial fibrillation, and left ventricular diastolic dysfunction (LVDD) was admitted with abdominal distention and lower extremity edema. He developed symptoms of acute circulatory failure, including low blood pressure, anuria, and skin spots. After positive fluid resuscitation, the blood pressure lowered further, and moist rales were audible over both lungs. Diagnosis: We performed bedside critical ultrasound for evaluation. The differential diagnoses based on the findings included left atrial and right heart dilatation, low cardiac output owing to reduced left ventricular ejection consequent to excessive circulatory capacity, right heart dilation, and left ventricular compression, and pulmonary edema caused by volume overload. Interventions: Infusion was withheld, and tracheal intubation and mechanical ventilation were instituted to assist breathing; reverse fluid resuscitation was initiated, using continuous renal replacement therapy (CRRT) to maintain a negative fluid balance. Outcomes: Within 72 hours of fluid withdrawal, the blood pressure reverted to normal, symptoms of pulmonary edema were alleviated, and the circulation and tissue perfusion were restored. The symptoms of acute renal injury are relieved and allowing urine formation without support. Lessons: Not all patients with acute circulatory failure require positive fluid resuscitation. Fluid balance should be closely monitored and managed. Potential intolerance to the rapid increase in volume may lead to biventricular interaction, ultimately leading to acute circulatory failure. The shock caused by volume overload should be treated with reverse fluid resuscitation. Combined echocardiography and LUS is a powerful tool for the differential diagnosis of circulatory and respiratory dysfunction.